2005
DOI: 10.1002/cyto.a.20146
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of T‐cell–mediated apoptosis in heterogeneous leukemia populations using four‐color multiparameter flow cytometry

Abstract: Background: The unique capacity of dendritic cells to present antigens to naive T cells is being increasingly utilized in cancer therapy. The efficacy of cell-based immunotherapy can be analyzed by determination of cytotoxic activity of T cells toward tumor cells in vitro. This study supplies a flow cytometric method to analyze T-cellmediated cytotoxic activity toward heterogeneous leukemic cell populations at a single-cell level. Methods: The fluorescent probe SYTO16 and the deadcell dye 7-aminoactinomycine-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Although not yet proven in clinical studies, in vitro data that we and others have generated show that AML-DC possess all the prerequisite functions needed to elicit an immune response in vivo (14,16,17). In a phase I pilot study on chronic myelogenous leukemia -derived dendritic cell vaccination in the advanced-stage disease, delayed type hypersensitivity responses representing autologous chronic myelogenous leukemia -specific T-cell responses were detected (27) However, clinical dendritic cell vaccination studies have, until now, shown limited success (18,19).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although not yet proven in clinical studies, in vitro data that we and others have generated show that AML-DC possess all the prerequisite functions needed to elicit an immune response in vivo (14,16,17). In a phase I pilot study on chronic myelogenous leukemia -derived dendritic cell vaccination in the advanced-stage disease, delayed type hypersensitivity responses representing autologous chronic myelogenous leukemia -specific T-cell responses were detected (27) However, clinical dendritic cell vaccination studies have, until now, shown limited success (18,19).…”
Section: Discussionmentioning
confidence: 91%
“…The ability of cultured T cells to kill leukemic blasts was evaluated in a flow cytometric cytotoxicity assay, as previously described (17). Briefly, AML-DC -stimulated T cells (effector cells) with or without 4-1BBL were cultured with corresponding AML blasts (target cells) at different effector to target cell ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Leukemic cells were harvested and taken up in PBS and apoptosis was induced by heat shock (2 h at 42°C) or by incubation for 2 h at 37°C with ARA-C (10 μg/ml; Mayne Pharma, Warwickshire, UK). The percentage of necrotic, apoptotic, and viable cells was determined before and after apoptosis induction by incubation with Syto-62 (5 nM; Molecular Probes, Eugene, OR), PSC833 (2 μM; Novartis, Basel, Switzerland) and 7-aminoactinomycin D (7-AAD; ViaProbe, Pharmingen, San Diego, CA) for 45 min at 37°C, and by flow cytometric analysis as described previously [28]. Syto-62 is a fluorescent nucleic acid stain that exhibits bright fluorescence upon binding to nucleic acids and is retained in viable cells.…”
Section: Methodsmentioning
confidence: 99%
“…22 Peripheral CD8 + T cells (effector cells) and bone marrow derived CD34 + blasts (target cells) were selected by magnetic separation (positive selection with CD8 and CD34 microbeads respectively, Miltenyi Biotec, Bergisch Gladbach, Germany). During this procedure also CD8 dim cells were selected resulting in effector population consisting of CD3 +…”
Section: Flow Cytometric Cytotoxic Assaymentioning
confidence: 99%